Hydrodynamic simulation of coastal reservoir in response to flow control: a numerical study of the Saemangeum reservoir - Yongsik Song; Semin Kim (Engineering Applications of Computational Fluid Mechanics)
Coastal reservoirs (CRs) are important water resources worldwide, but environmental problems can arise due to limited material mixing caused by the blocked propagation of tidal waves. The Saemangeum Reservoir is a large brackish reservoir in South Korea; owing to its complex fluctuation characteristics, accurate reproduction of its three-dimensional (3D) circulation and material distribution characteristics remains a challenge. Here, we aimed to improve the reproducibility of the Delft3D model through long-term precision monitoring and analyze problems occurring in CRs. The model reproduced the hydraulic flow and stratification phenomena in CRs. The Richardson number ([Formula: see text]) was higher than 100, and the Stratification Index ([Formula: see text]) was higher than 1 due to the density difference between the surface and bottom layers. The stratification strength of the Saemangeum Reservoir was, therefore, considered high. Moreover, a two-layer circulation occurred due to the strength of the eddy and the horizontal gradient of salinity. When the sluice gate was expanded, the area and number of days where hypoxia occurred decreased. It would also mitigate the retention of materials caused by the eddy and improve circulation. The findings of this study can be used as foundational data for solving and managing hydraulic problems within CRs.